2024
DOI: 10.3390/mi15040468
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Recent Developments in Magnetic Microrobots for Micro-/Nano-Manipulation

Ruomeng Xu,
Qingsong Xu

Abstract: Magnetically actuated microrobots have become a research hotspot in recent years due to their tiny size, untethered control, and rapid response capability. Moreover, an increasing number of researchers are applying them for micro-/nano-manipulation in the biomedical field. This survey provides a comprehensive overview of the recent developments in magnetic microrobots, focusing on materials, propulsion mechanisms, design strategies, fabrication techniques, and diverse micro-/nano-manipulation applications. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 219 publications
(236 reference statements)
0
2
0
Order By: Relevance
“…Magnetically levitated planar micromotors are core components supporting the development of integrated circuits, semiconductors, microfabrication, and other precision manufacturing equipment [ 1 , 2 ]. In recent years, with the rapid development of the precision manufacturing industry, magnetically levitated planar micromotors have become a hot research topic [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetically levitated planar micromotors are core components supporting the development of integrated circuits, semiconductors, microfabrication, and other precision manufacturing equipment [ 1 , 2 ]. In recent years, with the rapid development of the precision manufacturing industry, magnetically levitated planar micromotors have become a hot research topic [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have showcased the precise control of particle orientation through the application of magnetic fields [ 6 , 14 , 15 , 16 , 17 , 18 , 47 ]. In particular, magnetophoresis has been utilized to regulate the movement and direction of particles [ 9 , 43 , 47 , 48 , 49 , 50 ]. Additionally, research conducted in [ 14 , 15 , 16 , 47 ] demonstrated the utilization of a multi-solenoid system to energize magnetic fields.…”
Section: Introductionmentioning
confidence: 99%